Identification of DNA cis Elements Essential for Expansion of Ribosomal DNA Repeats in Saccharomyces cerevisiae - Kobayashi, Takehiko (American Society for Microbiology, 2001)
Saccharomyces cerevisiae carries ∼150 ribosomal DNA (rDNA) copies in tandem repeats. Each repeat consists of the 35S rRNA gene, the NTS1 spacer, the 5S rRNA gene, and the NTS2 spacer. The FOB1 gene was previously shown to be required for replication fork block (RFB) activity at the RFB site in NTS1, for recombination hot spot (HOT1) activity, and for rDNA repeat expansion and contraction. We have constructed a strain in which the majority of rDNA repeats are deleted, leaving two copies of rDNA covering the 5S-NTS2-35S region and a single intact NTS1, and whose growth is supported by a helper plasmid carrying, in addition to the 5S rRNA gene, the 35S rRNA coding region fused to the GAL7 promoter. This strain carries a fob1 mutation, and an extensive expansion of chromosomal rDNA repeats was demonstrated by introducing the missing FOB1 gene by transformation. Mutational analysis using this system showed that not only the RFB site but also the adjacent ∼400-bp region in NTS1 (together called the EXP region) are required for the FOB1-dependent repeat expansion. This ∼400-bp DNA element is not required for the RFB activity or the HOT1 activity and therefore defines a function unique to rDNA repeat expansion (and presumably contraction) separate from HOT1 and RFB activities.